Kinerja Pegawai Pusat Kesehatan Masyarakat Desa Bahonsuai Kecamatan Bumi Raya Kabupaten Morowali - Amalia, Nurul; Daswati; Rapi, Muhammad (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
The purpose of this research is to determine the performance of employees at Bahonsuai Community Health Center, Bumi Raya District, Morowali Regency. The research basis used is a qualitative research method with a descriptive type. The technique for determining informants is purposive sampling, and the informants in this research consist of 6 people.Based on the performance theory of Agus Dwiyanto (2008), the research results showthat (1) Productivity in the performance of Bahonsuai Community Health Center employees in Bumi Raya District, Morowali Regency is quite good, as seen from the speed of employees serving patients. However, the limitation of human resources, namely the insufficient number of doctors, affects the performance of the employees. Despite the limited number of doctors, the service provided by the employees still adheres to the applicable service standards. (2) The quality of service at Bahonsuai Community Health Center is quite good, indicated by the straightforward service flow that is easy for the community to understand. However, inadequate facilities andinfrastructure affect the performance of the Bahonsuai Health Center employees. (3) The responsiveness of Bahonsuai Health Center employees in Bumi Raya District, Morowali Regency is good. This can be seen from the ease and clarity of service information provided by the employees to patients. (4) The responsibility of Bahonsuai Health Center employees in Bumi Raya District, Morowali Regency is said to be good, as evidenced by the employees fulfilling their responsibilities well in serving patients. The employees are very friendly and empathetic when listening to patients' complaints. (5) The accountability of Bahonsuai Health Center employees in Bumi Raya District, Morowali Regency is good, as evidenced by the employees conducting monthly evaluations to improve and enhance their performance according to the responsibilities and operational standards applicable at Bahonsuai Health Center.